ATP and appetite: mitochondrial efficiency predicts meal size and the time until next feeding in common minnows - Ailsa Bell; Neil B. Metcalfe; Neal J. Dawson (Royal Society Open Science, 2025)
The predicted collapses of trophic food webs and diminished food availability, likely to be exacerbated by the effects of climate change, are of particular concern for aquatic species. Feeding behaviour influences how aquatic organisms respond to these conditions, and while the efficiency of various mitochondrial traits have been linked to growth outcomes and metabolic traits in fish, the role of mitochondrial function in influencing feeding behaviour is lesser known. Here, we used common minnows (Phoxinus phoxinus) to examine how liver and muscle mitochondrial function relates to the maximum amount of food consumed per meal by an individual and the time taken for appetite to return. Both the maximum meal size and appetite recovery time were positively related to muscle mitochondrial net phosphorylation efficiency. Appetite return time was also related to the maximum rate of oxidative phosphorylation; however, the relationship was positive in liver but negative in muscle. Our study shows that muscle mitochondrial efficiency influences feeding behaviours, where more efficient individuals can eat more, and eat less often. Identifying why certain individuals can consume more and return their appetite sooner may improve predictions of how individuals or populations of fish respond to food scarcity and trophic collapses.